Art Therapy on the Cognitive Function of Elderly with Dementia - Murdiyanti Prihatin Putri Dewi MPP (Alma Ata University Press, 2019)
The aging process continues as time goes by and there will be an impairment of the organ. Decreased body functions that often appear one of them is a decrease in cognitive function. Most of the elderly experienced dementia by showing changes in behavior. This study was to identify the effect of art therapy on cognitive function of the elderly with dementia with the design of this study was Quasy Experimental Pre-Post Control Goup Design. There were 82 respondents divided into control groups and intervention groups. Measurement of cognitive function of the elderly with dementia using the Mini-Mental State Examination (MMSE). The result of the research showed that there was a significant improvement of the cognitive function in elderly with dementia after art therapy for 4 (four) weeks. It can be concluded thatbrain exercise and art therapy exercise can be applied to increase cognitive function towards the elderly.